Characterisation of microvessel blood velocity and segment length in the brain using multi-diffusion-time diffusion-weighted MRI. Issue 8 (August 2021) - Scott, Lauren A; Dickie, Ben R; Rawson, Shelley D; Coutts, Graham; Burnett, Timothy L; Allan, Stuart M; Parker, Geoff JM; Parkes, Laura M
Multi-diffusion-time diffusion-weighted MRI can probe tissue microstructure, but the method has not been widely applied to the microvasculature. At long diffusion-times, blood flow in capillaries is in the diffusive regime, and signal attenuation is dependent on blood velocity (v ) and capillary segment length (l ). It is described by the pseudo-diffusion coefficient (D * = v l / 6 ) of intravoxel incoherent motion (IVIM). At shorter diffusion-times, blood flow is in the ballistic regime, and signal attenuation depends onv, and notl . In theory, l could be estimated usingD * andv . In this study, we compare the accuracy and repeatability of three approaches to estimatingv, and thereforel : the IVIM ballistic model, the velocity autocorrelation model, and the ballistic approximation to the velocity autocorrelation model. Twenty-nine rat datasets from two strains were acquired at 7 T, withb -values between 0 and 1000 smm −2 and diffusion times between 11.6 and 50 ms. Five rats were scanned twice to assess scan-rescan repeatability. Measurements ofl were validated using corrosion casting and micro-CT imaging. The ballistic approximation of the velocity autocorrelation model had lowest bias relative to corrosion cast estimates ofl, and had highest repeatability.